Predictors of adoption of zero-tillage system by farmers for risk adjustment in saline ecosystem: A discriminant analysis - PRIYADARSHNI, PRITI; PADARIA, R. N. (Journal of Soil and Water Conservation, 2020)
Increasing incidence of soil and water salinity has become a serious threat to crop production and livelihood security of farmers. The study was conducted in saline ecosystem of Mewat district of Haryana, where zero-tillage system in wheat could be used for risk adjustment. The study was conducted with survey of randomly selected 60 adopter and 60 non-adopter farmers with help of interview schedule. The adopters and non-adopters of zero-tillage technology in wheat differed significantly with respect to knowledge about the technology. The important predictors for adopters of zero-tillage technology in saline eco-system were identified as perceived ease of application of technology, perceived usefulness, risk orientation and access to machinery.